2021
DOI: 10.33590/emjhematol/21-00008
|View full text |Cite
|
Sign up to set email alerts
|

Glanzmann Thrombasthenia: A Case Report of a Rare Inherited Coagulation Disorder Presenting with Traumatic Head Injury

Abstract: This case study deals with a 32-year-old Indian male patient who presented with a traumatic head injury in the hospital, experienced uncontrolled bleeding after conducting surgery, and was eventually diagnosed with Glanzmann thrombasthenia. Glanzmann thrombasthenia is a rare hereditary blood clotting disorder characterised by a lack of platelet aggregation due to the absence of platelet glycoprotein IIb/IIIa. This occurrence is generally triggered by consanguineous marriages and is apparent in approximately on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…reported a complicated case of intracranial bleeding in a patient with undiagnosed GT, which required multiple surgical interventions to deal with the uncontrolled bleeding. [ 7 ] Like our first case, Fernández-Castellano et al . are the only ones to report spontaneous epidural bleeding in a known case of GT, but, in this case, the patient underwent two surgeries for two different EDHs during the same admission.…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations
“…reported a complicated case of intracranial bleeding in a patient with undiagnosed GT, which required multiple surgical interventions to deal with the uncontrolled bleeding. [ 7 ] Like our first case, Fernández-Castellano et al . are the only ones to report spontaneous epidural bleeding in a known case of GT, but, in this case, the patient underwent two surgeries for two different EDHs during the same admission.…”
Section: Discussionsupporting
confidence: 52%
“…[2] Similarly, Chakati et al reported a complicated case of intracranial bleeding in a patient with undiagnosed GT, which required multiple surgical interventions to deal with the uncontrolled bleeding. [7] Like our first case, Fernández-Castellano et al are the only ones to report spontaneous epidural bleeding in a known case of GT, but, in this case, the patient underwent two surgeries for two different EDHs during the same admission. [8] On the other hand, Yamahata et al did not report any difficulties in dealing with EDH in a 7-year-old girl who presented after falling; the patient underwent craniotomy with hematoma evacuation.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations